(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Phaseolus vulgaris, commonly mentioned as beans, is a profoundly hybridized garden vegetable in the Fabaceae family which is most widely used as food are currently being studied for additional physiological effects. The pharmacological significance of eating Phaseolus vulgaris has been intensively explored in order to identify several bioactive components responsible for their health benefits. Natural products either as pure compounds or as standardized plant extract, provide unlimited opportunities for new bioactive components primes because of its unmatched availability of chemical diversity. Plant compounds are of interest as a source of safer and effective substitutes than synthetically produced bioactive components. Gas chromatography-mass spectroscopy (GC-MS) is a tool capable of identifying active principles in plant’s extractions. Plants are the natural source of bioactive components responsible for the medicinal efficiency due to the presence of derivatives. One hundred and thirty-three compounds were detected in ethanolic extract of Phaseolus vulgaris where, 4-O-Methylmannose was identified as the major compound.